The Drosophila Selectin Furrowed Mediates Intercellular Planar Cell Polarity Interactions via Frizzled Stabilization. - Chin, M.L.; Mlodzik, M. (Developmental Cell, 2013)
Establishment of planar cell polarity (PCP) in a tissue requires coordination of directional signals from cell to cell. It is thought that this is mediated by the core PCP factors, which include cell-adhesion molecules. Here, we demonstrate that furrowed, the Drosophila selectin, is required for PCP generation. Disruption of PCP in furrowed-deficient flies results from a primary defect in Fz levels and cell adhesion. Furrowed localizes at or near apical junctions, largely colocalizing with Frizzled and Flamingo (Fmi). It physically interacts with and stabilizes Frizzled, and it mediates intercellular Frizzled-Van Gogh (Vang)/Strabismus interactions, similarly to Fmi. Furrowed does so through a homophilic cell-adhesion role that is distinct from its known carbohydrate-binding function described during vertebrate blood-cell/endothelial cell interactions. Importantly, the carbohydrate function is dispensable for PCP establishment. In vivo studies suggest that Furrowed functions partially redundantly with Fmi, mediating intercellular Frizzled-Vang interactions between neighboring cells.